Fighting for their survival - Christopher Whitlatch for IRF (Pachyderm)
The International Rhino Foundation (IRF), based in the United States operates on-the-ground programmes in Africa and Asia where rhinos live in the wild, supporting viable populations of the five remaining rhino species and the communities that coexist with them.